Zic3 enables bimodal regulation of tyrosine hydroxylase expression in olfactory bulb and midbrain-derived neurons - Smitha Bhaskar; Jeevan Gowda; Akshay Hegde; Surya Chandra Rao Thumu; Shreetama Banerjee; Helen M Bellchambers; Narendrakumar Ramanan; Paloma Merchan Sala; Kenneth Campbell; Stephanie Ware; Jyothi Prasanna; Anujith Kumar (Cell Death Discovery)
Abstract Tyrosine hydroxylase (TH) is the rate-limiting enzyme involved in the biosynthesis of catecholamines such as dopamine, norepinephrine, and epinephrine expressed in various regions of the brain, including the olfactory bulb (OB) and midbrain (MB). Previous studies demonstrated Zinc Finger transcription factor of the Cerebellum 3 (ZIC3) to regulate forebrain development, and Zic1/Zic3 compound mutant mice displayed reduced OB size. However, the precise role of ZIC3 in TH regulation remains elusive. In this study, we attempted to understand the role of ZIC3 in TH regulation and its underlying mechanism. While loss of function of Zic3 in OB-derived neurons led to down-regulation of TH expression, it could be rescued by over-expression of shRNA-resistant Zic3. Immunohistochemistry of OB of Zic3 null mice showed a similar reduction in expression of TH. Promoter of TH lacks the consensus ZIC3 binding region, and mechanistic insights revealed ZIC3 to regulate TH expression by interacting with ER81, a known TH regulator. ZIC3 interaction with ER81 is indispensable for ER81 binding to the Th promoter, and it fine-tunes ER81-mediated Th regulation in OB. In MB, where TH levels are highest after birth, ZIC3 regulates TH expression both in vitro and in vivo. TH was significantly reduced in P0 Zic3 null mice, as well as in Zic3 shRNA stereotactically delivered in 7-month-old mice. Mechanistically, in the absence of ER81 in MB, ZIC3 chooses an alternative approach of binding to Pitx3 promoter—a Dopaminergic (DA) fate determinant. Under the ectopic expression of ER81 in MB derived neurons, the propensity of ZIC3 binding to Pitx3 promoter is compromised, and its occupancy on Th promoter encompassing ER81 binding site is established, finally culminating in desired TH expression. Together, these findings reveal a unique ZIC3-mediated bimodal regulation of TH in OB and MB derived neurons.